2023
DOI: 10.1186/s13690-023-01092-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of birth interval on under-five mortality in east african countries: a propensity score matching analysis

Abstract: Background Under-five mortality remains a global public health concern, particularly in East African countries. Short birth interval is highly associated with under-five mortality, and birth spacing has a significant effect on a child’s likelihood of survival. The association between short birth intervals and under-five mortality was demonstrated by numerous observational studies. However, the effect of short birth intervals on under-five mortality has not been investigated yet. Therefore, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…In line with a study on under-five mortality from the EDHS 2016 report [28], the current study also revealed that a short preceding birth interval (i.e., a birth interval <24 months) was associated with an increased risk of under-five children's death compared to children born from mothers with a long preceding birth interval. This result was also consistent with another study carried out on the child mortality rate in Ethiopia [39] and with a study conducted to estimate the impact of birth interval on U5CM in East African countries [40], where the mortality rate of children under five years of age was lower among mothers who had optimal birth intervals.…”
Section: Discussionsupporting
confidence: 91%
“…In line with a study on under-five mortality from the EDHS 2016 report [28], the current study also revealed that a short preceding birth interval (i.e., a birth interval <24 months) was associated with an increased risk of under-five children's death compared to children born from mothers with a long preceding birth interval. This result was also consistent with another study carried out on the child mortality rate in Ethiopia [39] and with a study conducted to estimate the impact of birth interval on U5CM in East African countries [40], where the mortality rate of children under five years of age was lower among mothers who had optimal birth intervals.…”
Section: Discussionsupporting
confidence: 91%